2022
DOI: 10.1159/000528036
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Potential Role of Mesenchymal Stem Cells in Diseases of the Central Nervous System

Abstract: Introduction: Several studies indicate the role of mesenchymal stem cells (MSCs) as an important tool in regenerative medicine associated with injuries that affect the central nervous system (CNS). The MSCs have the capacity to differentiate into cells of the embryonal tissue, such as the mesoderm. So, these cells can be found in a variety of tissues. Also, the MSCs can release immunomodulatory and neurotrophic factors performance as inflammation mediators operating in injured tissue the regeneration. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 163 publications
0
7
0
Order By: Relevance
“…Several studies have shown the importance of stem cell transplantation. MSCs can play a vital role in controlling the immune response through the upregulation of neuroprotective cytokines like IL-10 and downregulating proinflammatory cytokines, TNF-α and IL-1, by releasing neurotropic factors and enhancing neurogenesis [38], and this is the same as for different neurological diseases [39,40]. Others showed that endogenous neural stem cells (NSCs) can differentiate directly into a mature neuron or indirectly into neural progenitor cells (NPCs) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the importance of stem cell transplantation. MSCs can play a vital role in controlling the immune response through the upregulation of neuroprotective cytokines like IL-10 and downregulating proinflammatory cytokines, TNF-α and IL-1, by releasing neurotropic factors and enhancing neurogenesis [38], and this is the same as for different neurological diseases [39,40]. Others showed that endogenous neural stem cells (NSCs) can differentiate directly into a mature neuron or indirectly into neural progenitor cells (NPCs) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the importance of stem cell transplantation. Mesenchyme stem cell MSCs can play a vital role in controlling immune response through the up-regulation of neuroprotective cytokines like IL-10 and down-regulating proinflammatory cytokines, TNF-α and IL-1 by releasing neurotropic factors and enhancing neurogenesis [21], and this is the same note in different neurological disease [22], [23]. Others showed that Endogenous neural stem cells (NSCs) can differentiate directly into a mature neuron or indirectly into neural progenitor cells (NPCs) [24], according to a study by Zhang, Qi, et al 2016, Using NSC implantation dramatically led to decline microgliosis and glial markers, proinflammatory cytokine (TNF-α, IL-6, IL-1) expressions and (TLR4) toll-like receptor 4 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in recent preclinical studies, de Munter et al [ 70 ] reported that bone marrow-derived stem/stromal cells exerted more of an anti-inflammatory effect on neurodegeneration conditions than did anti-inflammatory drugs. Thus, mesenchymal stem cells could have an immunomodulatory role to play in diseases of the brain [ 71 ]. Furthermore, Nebie et al [ 72 ] also recently discussed the potential for extracellular vesicles from platelets to improve neurological disorders.…”
Section: Are Nsc Similar To Msc and Behave Similarly Because They Are...mentioning
confidence: 99%